1971
DOI: 10.1104/pp.47.6.805
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Behavior of Isolated Avena Coleoptile Walls Subjected to Constant Stress

Abstract: In order to assess the role of the mechanical properties of the wail in auxin-induced cell elongation, a study has been made of the ability of isolated Arena coleoptile walls to extend (creep) when subjected to a constant applied stress. Creep occurs as a viscoelastic extension which has the following characteristics: the extension is proportional to log time and is partly reversible, and the extension rate has a Qio of about 1.05 and is markedly greater in auxin-pretreated walls. In nonconditioned walls the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Collenchyma cell walls have no linear components. A similar result was obtained and reported by Cleland with Avena coleoptiles (6). Therefore, the elongation of the collenchyma cells is not only due to exogenous stresses, but also requires a wall loosening as in the case of the epidermis (21).…”
Section: Resultssupporting
confidence: 89%
“…Collenchyma cell walls have no linear components. A similar result was obtained and reported by Cleland with Avena coleoptiles (6). Therefore, the elongation of the collenchyma cells is not only due to exogenous stresses, but also requires a wall loosening as in the case of the epidermis (21).…”
Section: Resultssupporting
confidence: 89%
“…When a constant stress is applied to a wall segment, initially, an almost instantaneous deformation occurs. This is then followed by further slower deformation or creep which can be reversible on removal of the stress (6,17). The same phenomenon occurs when strain is kept constant and stress relaxation is observed (15).…”
Section: Discussionmentioning
confidence: 85%
“…The instantaneous Young's modulus is therefore larger than the final equilibrium or stationary Young's modulus. It should be noted however that the value of the initial instantaneous Young's modulus can depend on how rapidly the strain or stress is applied (6,15). Haughton and Sellen (15) suggest that the instantaneous modulus could only be observed at times of I ms or less.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, empirical relations describing the experimental data can be a valuable alternative. In this way, Cleland (1971) observed that the extension of isolated Avena sativa walls behaves logarithmically in time. Others have used logarithmic functions to describe wall creep, the long-term and continuous deformation of cell walls (Bü ntemeyer et al, 1998;Thompson, 2001).…”
Section: Introductionmentioning
confidence: 91%
“…There are many examples of linear extension after expansin addition (McQueen-Mason et al, 1992;Li and Cosgrove, 2001), but the effect of expansin on A. xylinum material extension is not linear and seems logarithmic (Whitney et al, 2000). Interestingly, when only the effect of endogenous, untreated (e.g., not boiled) cell wall-loosening proteins was measured in the extensometer, by not treating (e.g., boiling) plant material, the extension application appeared logarithmic (Cleland, 1971;McQueen-Mason et al, 1992). It would be interesting to compare the activity of LTP and expansin directly.…”
Section: Ltp-mediated Cell Wall Looseningmentioning
confidence: 99%